2016
DOI: 10.1021/acs.jpcb.6b09363
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Solvent Effect on Ultrafast Charge Recombination Kinetics in Excited Donor–Acceptor Complexes

Abstract: Manifestation of the dynamic solvent effect (DSE) on the charge recombination (CR) kinetics of photoexcited donor-acceptor complexes in polar solvents has been investigated within the framework of the multichannel stochastic model. The model takes into account the reorganization of both the solvent and a number of intramolecular high-frequency vibration modes as well as their relaxation. The non-Markovian solvent dynamics is described in terms of two relaxation modes. The similarities and differences inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Indeed, MCSPT model simulations of the ultrafast CR kinetics in excited DACs have shown that the kinetic regularities of the charge transfer reactions occurring in nonequilibrium and equilibrium regimes can be strongly different. 14 In the present article such a regularity has been found and used for the first time as a strong evidence of the nonequilibrium mechanism of ultrafast CR. This regularity is associated with the dependence of the CR rate constant on dynamic properties of solvent, namely, on the solvent relaxation time.…”
Section: ■ Introductionsupporting
confidence: 54%
“…Indeed, MCSPT model simulations of the ultrafast CR kinetics in excited DACs have shown that the kinetic regularities of the charge transfer reactions occurring in nonequilibrium and equilibrium regimes can be strongly different. 14 In the present article such a regularity has been found and used for the first time as a strong evidence of the nonequilibrium mechanism of ultrafast CR. This regularity is associated with the dependence of the CR rate constant on dynamic properties of solvent, namely, on the solvent relaxation time.…”
Section: ■ Introductionsupporting
confidence: 54%
“…The data presented in Figure allow us to suggest several practical recommendations for achieving the maximum CS efficiency in dyads. The reorganization energy E rm of low-frequency modes, which are typically associated with solvent but can include large-amplitude intramolecular nuclear motions, should be small. The reorganization energy E rv of high-frequency intramolecular vibrations should also be small as can be achieved in molecules with rigid structure. The CS energy gap |Δ G CS2 | should be larger than the energy gap between LES2 and LES1. Since rapidly relaxing polar solvents generally accelerate CS in the Marcus normal region and weakly affect CR in the Marcus inverted region, , using rapidly relaxing solvents is preferred. …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Since rapidly relaxing polar solvents generally accelerate CS in the Marcus normal region and weakly affect CR in the Marcus inverted region, , using rapidly relaxing solvents is preferred.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Ultrafast transfer of charge (electron, proton, hole) is essential in fundamental science and diverse technological applications. Currently, there are emerging applications in the areas of electrocatalysis, solar energy conversion, and molecular electronics. Since the ultrafast electron transfer (ET) typically proceeds on a time scale comparable with that of the relaxation of solvent and intramolecular vibrations the nuclear nonequilibrium created by an excitation laser pulse or chemical transformation may be of paramount importance in such reactions. The regularities governing the kinetics of electron transfer occurring from nonthermalized solvent and nonequilibrium state of nuclear subsystem of the reactants can drastically differ from that of the thermal reactions. As a result, interest is growing in the study of such processes. , …”
Section: Introductionmentioning
confidence: 99%